Developing a system integration theory for enterprise - N. Yu. Lebedeva; E. S. Lobova (Вестник университета)
Provisions of the system integration theory for enterprise by G.B. Kleiner have been analyzed. The hypothesis about the impermanent position of the institutional subsystem relative to the cognitive subsystem in the sandwich pyramid of enterprise and its dependence on the stage of the life cycle has been put forward. The paper presents the results of approbation of application of G.B. Kleiner’s system integration theory for enterprise to the study of innovation-oriented enterprises development processes, as well as their interpretation in terms of the sandwich pyramid from the standpoint of a number of modern concepts of enterprise development management (I. Adizes, P. Senge, and Collins). The hierarchy of enterprise subsystems in the sandwich pyramid, which is characteristic of developing innovation-oriented enterprises and different from the author’s hierarchy, has been substantiated. It has been proved that the institutional subsystem of innovation-oriented enterprises has greater variability than the cognitive one. At the same time, knowledge determines institutions application, and not vice versa. It has been noted that such a hierarchy of subsystems is characteristic of economic systems that implement flexible approaches to project management, such as Agile. The statement that the hierarchy of enterprise subsystems presented by G.B. Kleiner is characteristic primarily for bureaucratic economic systems of hybrid management modes (in V.B. Sirotkin’s terminology) has been substantiated. According to I. Adizes’ life cycle model, ordinary enterprises become such at the stage of “aging” only.